Pesan-pesan Dakwah dalam Bahasa Tutur - Hikmat Hikmat (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2011)
Forwarding of The da’wah messages in oral language. Oral language in this context is transmitted, trasacted and transformated from relevan values. Even if the message of da’wah in oral language is culture frame that eksist in community, but its posite not outside of principles: qulan sadidan, Balighan, ma’rufan, kariman, layyinan, dab qoulan maysuran, that the message od da’wah can be manual by people dan followed it, because da’I is a available person for people followed it all.